A visual pollination mechanism of a new specialized pollinating weevil-plant reciprocity system - Yue, Jianjun; Yan, Zhen; Liu, Wei; Liu, Ju; Yang, Depo (Frontiers in Plant Science, 2024)
Pollinating flower-consuming mutualisms are considered exemplary models for studying coevolution due to their rarity. Visual cues are considered to have a major role in facilitating the evolution of floral patterns in these systems. We present a new specialized pollinating flower-consuming mutualism from the plant Wurfbainia villosa, which is a traditional Chinese herbal medicine, by a pollinating weevil, Xenysmoderes sp. Tests were conducted using color-preferring weevils in both indoor and outdoor field systems, and validation experiments were performed. Behavioral tests were conducted to investigate the role of the visual cues in the pollinator attraction of W. villosa, which is a self-compatible insect-pollinated plant that relies primarily on the Xenysmoderes sp. weevil for pollination due to its specialized gynandrium-like structure. Behavioral tests demonstrated that a blue color wavelength of 480 nm and the blue color system, as along with the UV-style pattern of the flowers, particularly the parts with specialized gynandrium-like structures in the labellum, were significantly attractive to both male and female weevils. These results were further confirmed through the field blue sticky board trap method. These findings indicated that the interaction between W. villosa and Xenysmoderes sp. weevil was a novel symbiotic relationship involving pollinator flower consumption. Additionally, Wurfbainia villosa flowers developed specific visual cues of UV patterns and specialized structures that played a crucial role in attracting pollinators.